SLIDE-Novel Approach to Apocrine Sweat Sampling for Lipid Profiling in Healthy Individuals - Kvasnička, Aleš; Friedecký, David; Tichá, Alena; Hyšpler, Radomír; Janečková, Hana; Brumarová, Radana; Najdekr, Lukáš; Zadák, Zdeněk (International journal of molecular sciences, 2021)
We designed a concept of 3D-printed attachment with porous glass filter disks-SLIDE (Sweat sampLIng DevicE) for easy sampling of apocrine sweat. By applying advanced mass spectrometry coupled with the liquid chromatography technique, the complex lipid profiles were measured to evaluate the reproducibility and robustness of this novel approach. Moreover, our in-depth statistical evaluation of the data provided an insight into the potential use of apocrine sweat as a novel and diagnostically relevant biofluid for clinical analyses. Data transformation using probabilistic quotient normalization (PQN) significantly improved the analytical characteristics and overcame the 'sample dilution issue' of the sampling. The lipidomic content of apocrine sweat from healthy subjects was described in terms of identification and quantitation. A total of 240 lipids across 15 classes were identified. The lipid concentrations varied from 10-10 to 10-4 mol/L. The most numerous class of lipids were ceramides (n = 61), while the free fatty acids were the most abundant ones (average concentrations of 10-5 mol/L). The main advantages of apocrine sweat microsampling include: (a) the non-invasiveness of the procedure and (b) the unique feature of apocrine sweat, reflecting metabolome and lipidome of the intracellular space and plasmatic membranes. The SLIDE application as a sampling technique of apocrine sweat brings a promising alternative, including various possibilities in modern clinical practice.
Keywords: mass spectrometry; Lipidomics; pot; Humans; odběr biologického vzorku; profiling; Healthy Volunteers; microsampling; Sweat; lidé; Lipids; lipidomika; apocrine sweat; metabolomika; zdraví dobrovolníci pro lékařské studie; lipidy; lipidomics; Specimen Handling; Metabolomics